Safety and Efficacy of Bevacizumab in Combination with First-Line Chemotherapy in Advanced Breast Cancer: Data from the Italian Cohort of the ATHENA Trial. Issue 4 (July 2014) - Sanna, Giuseppina; Fabi, Alessandra; Crivellari, Diana; Saracchini, Silvana; Battelli, Nicola; Nisticò, Cecilia; Capobianco, Alba Maria; Zampa, Germano; Bottini, Alberto; Del Prete, Salvatore; Simoncini, Edda; Galli, Anna; et al.
Aims and Background: The ATHENA international study investigated the safety and efficacy of bevacizumab plus first-line chemotherapy in locally recurrent/metastatic breast cancer in routine oncology practice. The present paper focuses on the outcomes of the Italian cohort of the study. Methods: A subgroup analysis was carried out to report on the safety (primary endpoint) and efficacy (secondary endpoint) outcomes of patients recruited from Italian Centers. Results: A total of 278 patients were included. Median age was 57 years (range, 26–85), and ECOG performance status was 0 or 1 in 96% of the patients. Bevacizumab was predominantly combined with a taxane monotherapy: paclitaxel (41.4%), docetaxel (21.9%), or a taxane-based combination therapy (12.2%). The most frequent grade ≥3 adverse events previously associated with bevacizumab were hypertension (3.2%), proteinuria (2.9%), and cardiac disorders (0.7%). Median time to progression was 10.9 months. Median overall survival was 29.9 months, and 1-year survival probability was 85%. Objective responses were observed in 62.6% of the patients, and an additional 30% achieved stable disease. Conclusions: Results from the study support the safety and efficacy of bevacizumab in combination with chemotherapy for the treatment of locally recurrent/metastatic breast cancer in the context of routine oncology practice in Italy.